Who's Next? : Guess Who! - Poitier, Anton; Touliatou, Sophia (Tulsa, OK : Kane Miller, a division of EDC Publishing, 2016)
"A delightful picture quiz book for young children. There are over 25 different creatures who come and go, and there are things to find on every page that will amuse and entertain, over and over again" --.
Keywords: Recollection (Psychology) -- Pictorial works; Animals -- Juvenile fiction